2017
DOI: 10.5603/gp.a2017.0097
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of microRNAs in triple-negative breast cancer

Abstract: Objectives: Triple-negative breast cancer (TNBC) is an aggressive subtype of breast cancer with limited treatment options and poor prognosis. TNBC is usually diagnosed at a relatively young age and is characterized by high risk of developing metastases. Some epigenetic regulation of gene expression is associated with TNBC. Expression of microRNAs (miRNAs) can serve as a potential tool for identifying critical biomarkers in TNBC.The aim of our study is to examine expression of selected miRNAs in TNBC and to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 33 publications
(38 reference statements)
3
40
0
Order By: Relevance
“…Moreover, it promotes tumor invasion and metastasis by regulating RECK (reversion‐inducing‐cysteine‐rich) and EVI5 (ecotrophic viral integration site 5) in hepatocellular carcinoma (Y. Li et al, ). Also, mir‐135b expression is found to be high when compared with normal breast tissue, suggesting that it might be associated with development and progression of TNBC (Paszek et al, ). Hsa‐miR‐18a promotes hepatocellular carcinoma cell migration and invasion by directly targeting Dicer 1 in vitro (X. Zhang, Yu, Zhang, Guo, & Li, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it promotes tumor invasion and metastasis by regulating RECK (reversion‐inducing‐cysteine‐rich) and EVI5 (ecotrophic viral integration site 5) in hepatocellular carcinoma (Y. Li et al, ). Also, mir‐135b expression is found to be high when compared with normal breast tissue, suggesting that it might be associated with development and progression of TNBC (Paszek et al, ). Hsa‐miR‐18a promotes hepatocellular carcinoma cell migration and invasion by directly targeting Dicer 1 in vitro (X. Zhang, Yu, Zhang, Guo, & Li, ).…”
Section: Discussionmentioning
confidence: 99%
“…BRCA1 is a tumor suppressor gene which, when mutated, is associated with a high sensitivity to breast cancer (Tanic et al, ). Several studies investigated the expression profile of miRNAs in TNBC tissues in comparison to the normal tissues (Paszek et al, ; Radojicic et al, ). In the present study, we explored the expression level of 667 microRNAs in TNBC tissues and compared it to that of normal tissues using TLDA.…”
Section: Discussionmentioning
confidence: 99%
“…vs normal tissues and showed that expression of some miRNAs plays a significant role in triple-negative primary breast cancers (Paszek et al, 2017;Radojicic et al, 2011). In this study, we screened the expression level of 667 different human miRNAs in TNBC tissues having wild type and mutated BRCA1 and normal breast tissues.…”
Section: Previous Reports Studied the Expression Level Of Mirnas In Tnbcmentioning
confidence: 99%
See 1 more Smart Citation
“…The dysregulation of miRNAs are involved in different cancer pathogenesis of solid tumors, such as apoptosis, inflammation, stress response, cell cycle, proliferation; the tumor microenvironment facilitates tumor development, differentiation, morphogenesis, progression and metastasis, and acted either in dominant or recessive roles, including breast cancer [16][17][18]. Emerging in vitro and in vivo studies open up a new area that miRNAs have the potential to serve as promising biomarkers for diagnosis and the development of novel anticancer drugs [19]. In this review, we attempt to summarize the potential clinical value and the roles of miRNAs involved in the pathogenesis of TNBC, such as the regulation of epigenetic mechanisms, epithelial-to-mesenchymal transition (EMT), maintenance of stemness, proliferation, metastasis, and apoptosis.…”
Section: Introductionmentioning
confidence: 99%